Trends and risk factors of global incidence, mortality, and disability of genitourinary cancers from 1990 to 2019: Systematic analysis for the Global Burden of Disease Study 2019 - Tian, Yi-Qun; Yang, Jin-Cui; Hu, Jun-Jie; Ding, Rong; Ye, Da-Wei; Shang, Ji-Wen (Frontiers in Public Health, 2023)
Abstract Background: With the development of treatment measures and the change of environment, the global burden of genitourinary cancers may have changed. Objective: To study and present estimates of the incidence, mortality, and disability of these four genitourinary cancers by location, age, and time period from1990 to 2019 and reveals the risk factors for the mortality of them. Materials: The Global Burden of Diseases Study 2019 was used to obtain data for this research. The prediction of cancer mortality and incidence was based on mortality to incidence ratios (MIRs). The MIR data was processed by logistic regression and adjusted by Gaussian process regression. The association between SDI and the incidence or disease burden was determined by Spearman’s rank order correlation. Results: Globally in 2019, there were 371.7 (131.7 for women and 240 for men) thousand kidney cancer incident cases, 524.3 (116.5 for women and 407.8 for men) thousand bladder cancer incident cases, 1410.5 thousand prostate cancer incident cases and 109.3 thousand testicular cancer cases, increasing by 4%, 29.1%, 22%, 45.5% respectively. The incidence rate of the four cancers and the burden of kidney cancer was positively correlated with the socio-demographic index. The contribution of high body-mass index to kidney cancer mortality has surpassed smoking to be the leading risk factor in the past thirty years. Smoking remained the leading risk factor for cancer-related mortality for bladder cancer and prostate cancer and the only risk factor for prostate cancer. However, the contribution of high fasting plasma glucose to bladder cancer mortality has been increasing. Conclusion: The incidence of bladder, kidney, prostate and testicular cancer is ever-increasing. High-income regions face more burden attributable to the four cancers. In addition to smoking, metabolic risk factors may need more attention.